1978
DOI: 10.1159/000241078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pharmacologic Agents on Umbilical Blood Flow in Fetal Lambs <i>in utero</i>

Abstract: We studied the effects of pharmacologic agents on umbilical blood flow and umbilical-placental vascular resistance in 18 fetal lambs in utero. Three groups of drugs were identified: the first had no effect on umbilical blood flow or umbilical-placental vascular resistance; the second altered umbilical blood flow secondary to changes in heart rate and placental perfusion pressure, but did not change umbilical-placental vascular resistance; the third decreased umbilical blood flow and increased umbilical-placent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Since the fetal renin-angiotensin system is well developed in late gestation (20) a physiological role of the peptide in the fetal placental flow regulation could be expected. This is supported by findings in animals showing exogenously administered AT to cause fetal placental vasoconstriction (16,29,85,126,153), and also by AT-induced vasocontraction in isolated human umbilical, chorionic and stem villous arteries (V111,3,152, Fig. 3).…”
Section: Effects Of Angiotensin I1supporting
confidence: 58%
“…Since the fetal renin-angiotensin system is well developed in late gestation (20) a physiological role of the peptide in the fetal placental flow regulation could be expected. This is supported by findings in animals showing exogenously administered AT to cause fetal placental vasoconstriction (16,29,85,126,153), and also by AT-induced vasocontraction in isolated human umbilical, chorionic and stem villous arteries (V111,3,152, Fig. 3).…”
Section: Effects Of Angiotensin I1supporting
confidence: 58%
“…Increases in the plasma ANP concentration have been shown to increase plasma renin activity (12). If ANP also increases angiotensin I1 concentrations, this may be one mechanism contributing to the increase in umbilicalplacental vascular resistance (20). Because the activity of other vasoactive hormones may have been altered by ANP infusion in these studies, the responses we observed were probably a combination of ANP and other hormone effects.…”
Section: Discussionmentioning
confidence: 63%
“…It is possible that sympathetic mechanisms may have mediated the increase in peripheral vascular resistance in the fetus. However, because infusions of epinephrine and norepinephrine do not directly alter umbilical-placental vascular resistance (20), some other mechanism(~) may also be involved. Increases in the plasma ANP concentration have been shown to increase plasma renin activity (12).…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the strong direct relation between fetal heart rate and umbilical flow noted by Berman et al, (28). This may reflect the strong direct relation between fetal heart rate and umbilical flow noted by Berman et al, (28).…”
Section: Discussionmentioning
confidence: 82%
“…These authors (28) have proposed that umbilical vascular impedance increases as heart rate decreases, independent of caliber changes of placental resistance vessels. This explanation has been challenged (29).…”
Section: Discussionmentioning
confidence: 99%